Underappreciated Factors to Consider in Revision Anterior Cruciate Ligament Reconstruction: A Current Concepts Review. Issue 1 (24th January 2018) - Southam, Brendan R.; Colosimo, Angelo J.; Grawe, Brian
Primary anterior cruciate ligament (ACL) reconstructions (ACLRs) are being performed with increasing frequency. While many of these will have successful outcomes, failures will occur in a subset of patients who will require revision ACLRs. As such, the number of revision procedures will continue to rise as well. While many reviews have focused on factors that commonly contribute to failure of primary ACLR, including graft choice, patient factors, early return to sport, and technical errors, this review focused on several factors that have received less attention in the literature. These include posterior tibial slope, varus malalignment, injury to the anterolateral ligament, and meniscal injury or deficiency. This review also appraised several emerging techniques that may be useful in the context of revision ACL surgery. While outcomes of revision ACLR are generally inferior to those of primary procedures, identifying these potentially underappreciated contributing factors preoperatively will allow the surgeon to address them at the time of revision, ideally improving patient outcomes and preventing recurrent ACL failure.